Edukasi dan Skrining Hipertensi untuk Meningkatkan Pengetahuan Masyarakat di Dusun Gemawang, Sinduadi, Mlati, Sleman - Parastri, Chantika; Dewi P. , Chantika; Nuraini; Syaputri , Widya; Ramadhani, Lailatul; Budi P., Renaldi Tri; Ismi , Nur; Nuraida P. , Syifa; Miftakhul P., Rendy; Putri K., Tiara Eka; Riyadi, Sujono (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Hypertension is a non-communicable disease that has a high risk of causing serious complications if not controlled. Education and early screening are needed to increase community awareness and understanding of this disease. This activity aims to improve the knowledge of the Gemawang Hamlet community about hypertension and encourage early detection behavior through blood pressure checks. The methods applied included interactive health education sessions, filling out pre-post-test questionnaires, and blood pressure screening for 58 participants. The results showed that 56.9% of the participants had high blood pressure, and only 22 individuals were aware of the symptoms of hypertension. This activity affectively enhanced public knowledge and served as a preventive effort against complications related to hypertension.